EDUCATION, HUMAN RIGHTS AND YOUTH: UZBEKISTAN'S REFORM STRATEGY - Фирюза Мухитдинова (Bright Mind Publishing, 2025)
The article discusses the system of education and training and reforms in the field of education at the present stage of the Republic of Uzbekistan. The legal framework for teaching from childhood on human rights and how youth, education and human rights are analyzed: they are considered in the new reforms of Uzbekistan. The main directions of the right to education in the Development Strategy of Uzbekistan, as well as in the state program of 2025 aimed at improving education, protecting human rights and supporting youth, is a set of measures focused on the development of key aspects of the country's social and educational policy. In the field of education, special attention is paid to updating curricula, maintaining the quality of teaching and access to education at all levels. Human rights reforms focus on the judiciary, protection against corruption and the protection of civil law, which contributes to the creation of a more just society. Youth potential is a critical resource for the development of the country, and therefore reforms include initiatives aimed at increasing opportunities for youth participation in political, social and economic life. These measures are aimed at ensuring a more dignified and inclusive future for Uzbekistan, improving the quality of life of its citizens and the position between peoples.